2011
DOI: 10.1111/j.1447-0594.2011.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Can the New Cooperative Medical Scheme promote rural elders' access to health‐care services?

Abstract: The aim of the present study was to examine the impact of the New Cooperative Medical Scheme (NCMS) on rural elders' access to health-care services. Articles were identified from PubMed, Elsevier, Wiley, EBSCO, EMBASE, SCI Expanded, ProQuest, Google, and CNKI which is the most informative database in Chinese, with the search terms "rural", "China", "old", "older", or "elder", "elderly", or "aged", "aging", "medical insurance", or "community-based medical insurance", or "cooperative medical scheme". Related web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…That is, the offspring has responsibilities to care for elders (filial piety) and the same generation (e.g., spouse and sibling) should care for each other in the extended family (Dai, Zhou, & Mei, 2013;Dai, Zhou, Mei, Wu, & Mao, 2011). By implementing these family responsibilities, Chinese set an example to the offspring and get positive feelings (e.g., satisfaction) from family caregiving.…”
Section: Discussionmentioning
confidence: 96%
“…That is, the offspring has responsibilities to care for elders (filial piety) and the same generation (e.g., spouse and sibling) should care for each other in the extended family (Dai, Zhou, & Mei, 2013;Dai, Zhou, Mei, Wu, & Mao, 2011). By implementing these family responsibilities, Chinese set an example to the offspring and get positive feelings (e.g., satisfaction) from family caregiving.…”
Section: Discussionmentioning
confidence: 96%
“…20 A literature review concluded that NCMS increased healthcare utilization by rural elders, but that affordability challenges remained, especially among the poorest. 21 Another study of NCMS' impact found an increased use of preventive care, but not of formal healthcare services. 22 Studies to date have also reported conflicting evidence on the effects of NCMS on risk protection.…”
Section: Impact Of Ncmsmentioning
confidence: 99%
“…China's BNMI system reform is advancing steadily, including BNMI coverage expansion, and has achieved remarkable results; however, there are also deficiencies in the system. China's BNMI system mainly comprises the urban resident basic medical insurance and the rural cooperative medical insurance [23,24,25,26]. The BNMI system covers more than 1 billion of the country's 1.3 billion populations, as a report issued by the Ministry of Health showed [27].…”
Section: Discussionmentioning
confidence: 99%